2012
DOI: 10.18267/j.efaj.8
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Management Accounting Development during Last 30 Years

Abstract: This paper analyses some reasons why strategic management accounting was not widely accepted. After initial boom of strategic management accounting there is stagnation in recent year. Application of strategic management accounting in practice does not exceed pilot case study. Strategic management accounting lessons are not commonly included in educational programs. Finally researches on strategic management accounting have only limited results. Paper is based on literature review and empirical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
3
0
6
Order By: Relevance
“…They further highlighted four standout features: competitors, long-run, processes and customer orientation. Other studies (Šoljakova, 2012;Fowzia, 2011) attempted to review the SMA technique usage. For instance, Fowzia (2011) noted that some SMA techniques can influence the financial performance of a firm but the intensity of usage may vary among different countries.…”
Section: Strategic Management Accounting (Sma)mentioning
confidence: 99%
“…They further highlighted four standout features: competitors, long-run, processes and customer orientation. Other studies (Šoljakova, 2012;Fowzia, 2011) attempted to review the SMA technique usage. For instance, Fowzia (2011) noted that some SMA techniques can influence the financial performance of a firm but the intensity of usage may vary among different countries.…”
Section: Strategic Management Accounting (Sma)mentioning
confidence: 99%
“…Ahmad and Roghayeh (2010) found in their study that managers of the listed companies in Tehran stock exchange used the traditional management tools. Soljakova (2012) found the main reasons for the non widespread of applying SMA is because of there is no agreement between writers about SMA definition, unclear methods and the un efficient managers to apply it or its tools. Also, Gary et al (2003) found in his study that 76% of the companies in his study use quantitative techniques (spread sheet), 70% of them use operation budgeted and direct labor to allocate over head costs, and 25% use target costing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Αυτό είναι και το βασικό χαρακτηριστικό που ουσιαστικά τη διαφοροποιεί από προγενέστερες προσπάθειες που στόχευαν στη δημιουργία μιας προσέγγισης που να συνδυάζει τη λογιστική με τη διοίκηση (Khodzytska & Ivchenko 2014, Soljakova 2012, Roslender & Hart 2002.…”
Section: η στρατηγική διοικητική λογιστική (Strategic Management Accounting)unclassified
“…H έννοια της στρατηγικής διοικητικής λογιστικής είναι δύσκολο να οριστεί με ακρίβεια, καθώς συνδυάζει ποικίλα στοιχεία της σύγχρονης διοικητικής λογιστικής και της υπάρχουσας βιβλιογραφίας για τη στρατηγική. Άλλωστε, 'δεν υπάρχει ένα κοινώς αποδεκτό εννοιολογικό πλαίσιο που να προσδιορίζει με σαφήνεια την έννοια της στρατηγικής διοικητικής λογιστικής' (Soljakova 2012, Tomkins & Carr 1996. Ακόμα, είναι χαρακτηριστικό, ότι η συγκεκριμένη έννοια απουσιάζει από τη βιβλιογραφία της βορείου Αμερικής, με εξαίρεση τα έργα των Kawada & Johnson (1993) και Pearson (1997).…”
Section: η στρατηγική διοικητική λογιστική (Strategic Management Accounting)unclassified
See 1 more Smart Citation